Creep-resistant dextran-based polyurethane foam as a candidate scaffold for bone tissue engineering: Synthesis, chemico-physical characterization, and in vitro and in vivo biocompatibility. Issue 14 (21st September 2016) - Gerges, I.; Tamplenizza, M.; Lopa, S.; Recordati, C.; Martello, F.; Tocchio, A.; Ricotti, L.; Arrigoni, C.; Milani, P.; Moretti, M.; Lenardi, C.
ABSTRACT: A highly crosslinked composite dextran-based scaffold (named DexFoam) was tailored to overcome specific deficiencies of polymeric and ceramic bone scaffolds and to guarantee a bone-mimicking microenvironment for the proliferation of human mesenchymal stem cells in vitro . The creep resistance for up to 90% compressive stain, the capability to regain the original shape after deformation, and the good thermal stability in both physiological and "body limit" conditions make DexFoam a valid alternative to the currently available bone scaffolds. Histopathological evaluation for host reaction and tissue colonization of DexFoam scaffold, implanted subcutaneously in mice, demonstrated its in vivo biocompatibility and biodegradability. GRAPHICAL ABSTRACT: